PERBANDINGAN KONDISI PETANI, USAHATANI DAN AKSES PASAR MANGGA DI KECAMATAN GREGED DAN JAPARA - Elly Rasmikayati; Ahmad Choibar Tridakusumah; Mochamad Dafa Zikriawan Purnama; Eddy Renaldi; Bobby Rachmat Saefudin (Universitas Galuh Ciamis, 2021)
Greged District, Cirebon Regency and Japara District, Kuningan Regency are included in the mango production centers in West Java. Both areas have their respective potentials and weaknesses in terms of farmers, farming and market access characteristics. The purpose of this study was to compare the conditions of farmers, farming and market access of mangoes in Greged and Japara Districts. The research method uses quantitative research methods using survey methods. The sample of farmers was determined using simple random sampling technique. There were 130 samples of mango farmers for each population. The analytical tools used in this study are Descriptive Analysis of Frequency Distribution, Two Samples T Test and Mann-Whitney U Test. The results of this study indicate that the condition of farmers and mango farming in Greged District is significantly different from Japara District in all variables analyzed, namely gender, age, main occupation, farm income, number of trees owned. Meanwhile, for market access, there are 2 significantly different variables, namely the distance to the market and the travel time to the market.